2022
DOI: 10.1108/k-05-2022-0717
|View full text |Cite
|
Sign up to set email alerts
|

Disruption in family life due to despotic leadership and COVID-19: the mediating role of emotional exhaustion

Abstract: PurposeThe fear of COVID-19, being an emerging research variable and a parcel of the ongoing pandemic, has not yet been fully studied with respect to leadership and employee family life. Based on the conservation of resources theory, the current study aims to investigate the relationship between despotic leadership and work-family conflict under the context of fear prevailing due to COVID-19. The paper also highlights the mediating role of emotional exhaustion between the two variables.Design/methodology/appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…Chaudhary and Islam (2022 b) noted that almost 95% of nurses encountered negative leadership styles at work including despotic leadership; as a result, 75% of the workforce engage in bullying behavior (Syed et al, 2020). Nevertheless, there is still a need to comprehend how negative leadership affects nurses' well-being in Pakistan (Rafiq et al, 2022). Thus, this study extends the literature by identifying the most common and unreported negative behaviors of nurse leaders such as despotic (Pishgooie et al, 2019).…”
Section: R E T R a C T E Dmentioning
confidence: 60%
See 1 more Smart Citation
“…Chaudhary and Islam (2022 b) noted that almost 95% of nurses encountered negative leadership styles at work including despotic leadership; as a result, 75% of the workforce engage in bullying behavior (Syed et al, 2020). Nevertheless, there is still a need to comprehend how negative leadership affects nurses' well-being in Pakistan (Rafiq et al, 2022). Thus, this study extends the literature by identifying the most common and unreported negative behaviors of nurse leaders such as despotic (Pishgooie et al, 2019).…”
Section: R E T R a C T E Dmentioning
confidence: 60%
“…It was observed that fear of COVID-19 has significantly impacted mental health and well-being over the previous three years T E D (Xing et al, 2020). However, the employees of the health-care industry experienced worst crisis during COVID-19 pandemic (Rafiq et al, 2022) as compared to any other industry, especially nurses. Nurses were required to work closely with COVID-19 patients (Sarwar et al, 2020).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…The age and gender of the respondents were utilized as control variables taking the lead from earlier similar studies (e.g. Rafiq et al ., 2022; Sarwar et al. , 2022b) to ensure that the relations between the variables and overall results were not confounded.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we have collected time-lagged data in two waves following the footsteps of similar previous studies (Rafiq et al, 2022;Sarwar et al, 2022b), however, future researchers are suggested to use 3 waved data collection to further reduce any chances of bias in data. Similarly, future studies may use key control variables other than demographic variables in order to further reduce the confounding effects on the tested relationships.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation